Performance of laminated super-fast dried oil palm lumber by using thermoplastic polymers as binding agent - Wong, Mui Leng (2018)
Laminated lumber has uniform properties and higher strength which make it a superior structural wood composite product than other solid timber or glue-laminated timber. However, due to formaldehyde emission of commercial adhesive and reduction of log production from forest, efforts have been made to use alternative materials such as oil palm trunk to produce laminated board with thermoplastic polymer as binding agent. This study was undertaken to determine the gluing condition and physio-mechanical properties of laminated super-fast dried oil palm lumber by using thermoplastics as binding agent. In this study, two different types and forms of thermoplastics were used as binding agent for laminated super-fast dried oil palm lumber. The results revealed that laminated super-fast dried oil palm lumber with optimum physical (thickness swelling and water absorption) and mechanical properties (bending properties and shear strength) was produced using high density polyethylene in powder forms as binding agent.